2020
DOI: 10.1038/s41419-020-2689-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ENST00000563492 promoting the osteogenesis–angiogenesis coupling process in bone mesenchymal stem cells (BMSCs) by functions as a ceRNA for miR-205-5p

Abstract: Pain, physical dysfunction, and mental disorders caused by bone nonunion bring great burden to patients. Bone mesenchymal stem cells (BMSCs) isolated from bone nonunion patients with poor proliferation and osteogenic ability are compared with that from normal bone-healing patients. Long noncoding RNAs (lncRNAs) are a class of RNAs that are more than 200 nucleotides in length, lack an open-reading frame encoding a protein, and have little or no protein-coding function, and could regulate gene expression, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…More importantly, previous data have also documented that miR‐205‐5p works as an anti‐tumor miRNA to regulate the progression of PCa 19 . Meanwhile, it is also noteworthy that miR‐205‐5p bound by lncRNA ENST00000563492 has been shown to facilitate the osteogenesis in BMSCs 46 . Furthermore, our experimental findings demonstrated that NEAT1 inhibited miR‐205‐5p to promote the activity of ALP and mineralization of extracellular matrix and continuously upregulated the mRNA levels of RUNX2, ALP, COL1A1, and OCN, thereby contributing to osteogenic differentiation of hBMSCs and presenting a promising target for therapeutics through this axis.…”
Section: Discussionmentioning
confidence: 94%
“…More importantly, previous data have also documented that miR‐205‐5p works as an anti‐tumor miRNA to regulate the progression of PCa 19 . Meanwhile, it is also noteworthy that miR‐205‐5p bound by lncRNA ENST00000563492 has been shown to facilitate the osteogenesis in BMSCs 46 . Furthermore, our experimental findings demonstrated that NEAT1 inhibited miR‐205‐5p to promote the activity of ALP and mineralization of extracellular matrix and continuously upregulated the mRNA levels of RUNX2, ALP, COL1A1, and OCN, thereby contributing to osteogenic differentiation of hBMSCs and presenting a promising target for therapeutics through this axis.…”
Section: Discussionmentioning
confidence: 94%
“…During this process, the expression of VEGF improves the coupling process of osteogenesis and angiogenesis. 106 Studies have revealed that MIR22HG expression is significantly reduced in BMSCs of osteoporotic mice and upregulated in hBMSCs during osteogenic differentiation. 107 In addition, a considerable quantity of literatures have described MSCs have the abilities not only in osteogenic differentiation, but also in adipogenic, myogenic and chondrogenic differentiation.…”
Section: The Role Of Lncrnas In Osteogenesismentioning
confidence: 99%
“…Currently, stem cell-based tissue engineering reconstruction of bone defect is a feasible and continuously developing strategy to restore structure and function [3]. Bone marrow mesenchymal stem cells (BMSCs), a seed of bone regeneration, can differentiate into osteoblasts and secrete angiogenic factors to promote bone regeneration [4][5][6]. Thus, the BMSCs have potential to couple the osteogenesis and angiogenesis processes.…”
Section: Introductionmentioning
confidence: 99%